The Evolution of Endothelial Therapeutics - Moloney, Greg; Sylvestre-Bouchard, Antoine; Holdsworth, Mary (Canadian Eye Care Today, 2025)
Corneal endothelial diseases comprise a spectrum of conditions that critically affect the health and transparency of the cornea, posing unique challenges for ophthalmologists. The most prevalent among these is Fuchs’ endothelial corneal dystrophy (FECD), which accounts for approximately 39% of all corneal transplants globally. Bullous keratopathy (BK) can affect the entire cornea, leading to painful blisters that may become infected. Other rarer pathologies, such as iridocorneal endothelial syndrome, posterior polymorphous corneal dystrophy, and congenital hereditary endothelial dystrophy, present unique diagnostic and therapeutic challenges. Additionally, graft failure remains a notable indication for treatment. High-risk cases experience failure rates exceeding 35% within 3 years, with endothelial rejection accounting for half of the cases. Corneal transplants have been considered the gold standard for decades, with advancements in surgical techniques leading to shorter operating times, faster visual recovery, and improved outcomes. However, the growing global shortage of transplant-grade donor tissue further complicates treatment, underscoring the urgent need for innovative approaches such as genetic and cell-based therapies.